Estudio de la reception del saque en el voleibol masculino espanol de elite tras la incorporacion del jugador libero - Urena, E.; Calvo Ferrer, R. M.; Lozano Perez, C. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2002)
This piece of research is concerned with the National Championship of the Spanish Male Premier League held during the season 1998/99. Its main objective is to identify and study those variable affecting performance in serve reception in the case of Spanish male teams. Moreover, results can be considered to particulary interesting, because since season 1998/1999 Volleyball in Spain applied one of the most remarkable and controversial rules in his history: the libero player.